Analisis Kesiapan Guru Dalam Menghadapi Tantangan Kurikulum Merdeka: Perspektif Guru Sekolah Dasar - Rahma Aulia; Putri Andini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The introduction of the Independent Curriculum brought substantial changes to Indonesia's educational landscape. The main challenge faced by elementary school teachers in implementing the Independent Curriculum is changing the traditional paradigm into a student-centred learning approach. The aim of this research is to provide insight into the level of readiness of elementary school teachers in facing the implementation of the Independent Curriculum and identify the challenges. This research also provides an understanding of teachers' perceptions of resource support as well as the factors and impacts on teacher readiness in implementing the Independent Curriculum. The data collection method in this research uses questionnaires and the research target is elementary school teachers. By conducting this research, respondents expressed the view that the impact of the Merdeka Curriculum was very positive on the learning process and this raised a sense of optimism about the future of education with the implementation of the Merdeka Curriculum.